The establishment of Bolshevik power on the Russian periphery: Soviet Karelia, 1918-1919 - Wright, Alistair S. (2012)
Using an array of original materials from Russian regional and central archives this detailed study of Soviet Karelia from 1918-1919 is the first to appear in English after the fall of the Soviet Union. It adds to the still limited number of regional studies of the civil war period and using the Karelian districts as a case study discusses how the Bolsheviks consolidated power on the periphery, what factors hindered this process and what were the sources of resistance. Karelia is unique for a combination of reasons. First, it is a grain deficit region and so was always in need of help with the supply of grain from the Volga and other parts of central Russia. Second, the political influence of the Left Socialist Revolutionary party (Left SRs) continued for a considerable time after the events of July 1918. The thesis explores how power was transferred in the region following the October revolution and how the planned political objectives of the Bolsheviks were stalled by the lack of political control in the districts not least of all, for most of 1918, because of the influence of the Left SRs. However, despite political, economic, social and military crises the Bolsheviks gained more experience in power as the civil war progressed and a semblance of order emerged from the chaos. They gained enough control over the food supply shortages for the population to subsist and increased their control in key Soviet institutions, such as the provincial security police (the Cheka) and the Red Army, which ultimately ensured the survival of the Bolshevik regime and victory in the civil war.